Inotuzumab ozogamicin with bosutinib for relapsed or refractory Philadelphia chromosome positive acute lymphoblastic leukemia or lymphoid blast phase of chronic myeloid leukemia. Issue 8 (28th May 2021) - Jain, Nitin; Maiti, Abhishek; Ravandi, Farhad; Konopleva, Marina; Daver, Naval; Kadia, Tapan; Pemmaraju, Naveen; Short, Nicholas; Kebriaei, Partow; Ning, Jing; Cortes, Jorge; Jabbour, Elias; et al.
Abstract: Relapsed/refractory (R/R) Philadelphia chromosome positive acute lymphoblastic leukemia (Ph + ALL) and lymphoid blast phase of chronic myeloid leukemia (LBP‐CML) have poor outcomes. We designed a phase 1/2 study combining inotuzumab ozogamicin with bosutinib for this patient population. Patients with T315I mutation were excluded. Bosutinib was administered daily at three dose levels (300 mg/d, 400 mg/d, 500 mg/d) in a 3 + 3 design. Inotuzumab ozogamicin was dosed weekly during cycle one, and once every 4 weeks subsequently for a total of six cycles. The primary objective was to determine the safety and the maximum tolerated dose (MTD) of bosutinib in combination with inotuzumab ozogamicin. Eighteen patients were enrolled (Ph‐positive ALL, n = 16; LBP‐CML, n = 2). The median age was 62 years (range, 19–74) and the median number of prior therapies was one (range, 1–5). Dose limiting toxicities included grade 3 skin rash and bosutinib 400 mg daily was determined as the MTD. The most frequent grade 3/4 treatment‐emergent adverse events were thrombocytopenia (60%) and neutropenia (38%). A complete response (CR) / CR with incomplete count recovery (CRi) was achieved in 15/18 (83%) patients; 11/18 (61%) patients achieved negative measurable residual disease by flow cytometry. Complete molecular response was noted in 10/18 (56%) patients. The 30‐day mortality was 0%. After a median follow‐up of 44 months, the median duration of response and overall survival were 7.7 months and 13.5 months, respectively. Six patients had a subsequent allogeneic stem cell transplant. No patient developed veno‐occlusive disease. Inotuzumab ozogamicin with bosutinib was well tolerated in R/R Ph‐positive ALL and LBP‐CML.